NILAI-NILAI FUNDAMENTAL DAN PENGARUHNYA TERHADAP BETA SAHAM SYARIAH PADA JAKARTA ISLAMIC INDEKS - Fidiana Fidiana (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
The objective of this research is to examine influenced fundamental variables (leverage, earnings variability, accounting beta, earnings per share, price earnings ratio, price book value, dividend yield, and trading volume) on syariah stock beta as proxy of systematic risk. Samples used in this research are selected using purposive sampling from public companies of Jakarta Islamic Index (JII) from 2001-2005.The research tested hypotheses by using multiple regression analysis models. Based on model used, the results with F-test or ANOVA show that fundamental variable significant influence on syariah stock beta. The results also show that from the eight factors of fundamental variable assumed to influence on syariah stock beta, there are four factors which partially show significant influence consist of: leverage, earnings variability, price book value, and trading volume